Common Marmoset Cell Lines and Their Applications in Biomedical Research - Ekaterina Bayurova; Alla Zhitkevich; Daria Avdoshina; Natalya Kupriyanova; Yuliya Kolyako; Dmitry Kostyushev; Ilya Gordeychuk (Cells, 2023)
Common marmosets (Callithrix jacchus; CMs) are small New World primates widely used in biomedical research. Early stages of such research often include in vitro experiments which require standardized and well-characterized CM cell cultures derived from different tissues. Despite the long history of laboratory work with CMs and high translational potential of such studies, the number of available standardized, well-defined, stable, and validated CM cell lines is still small. While primary cells and immortalized cell lines are mostly used for the studies of infectious diseases, biochemical research, and targeted gene therapy, the main current applications of CM embryonic stem cells and induced pluripotent stem cells are regenerative medicine, stem cell research, generation of transgenic CMs, transplantology, cell therapy, reproductive physiology, oncology, and neurodegenerative diseases. In this review we summarize the data on the main advantages, drawbacks and research applications of CM cell lines published to date including primary cells, immortalized cell lines, lymphoblastoid cell lines, embryonic stem cells, and induced pluripotent stem cells.